E-health status in the information society and its future prospects - Ali Tandiseh Bana (Mashhad University of Medical Sciences, 2017)
E-health one of the important applications of information and communication technologies (ICT) in the field of public health services and treatment that projects its launch, within the framework of a comprehensive e-government program and runs the Information Society. Thus, e-health, including health services and health information via the Internet. Therefore, the availability of and prospects for the future information society in preparation for implementation of e-health, information society is essential. The aim of this study was to investigate the introduction of e-health in the information society and its associated aspects as well as the development of e-health and future prospects. Continue to assess the impact of each of these aspects will be addressed in the development of the health sector, aspiration and vision development. Paper Type: letter to editor.